THE EFFECT OF USING ICE BREAKING ON STUDENTS’ MOTIVATION IN ENGLISH LEARNING IN JUNIOR HIGH SCHOOL - Mesyela Niken Elfayeni; Melyann Melani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to discover the effect of using ice breaking activities on students’ motivation in learning English. The study was conducted because preliminary observations revealed that many students showed low motivation in English class, often due to boredom, anxiety, and fear of peer judgment. This lack of motivation impacted their participation and learning outcomes. To address this issue, the researcher applied ice breaking as an engaging and interactive teaching strategy to create a fun and comfortable classroom atmosphere. This research used a quasi-experimental design with pre-test and post-test control group design. The population was eighth-grade students of SMPN 6 Bukittinggi, consisting of 190 students. The sample included two classes: VIII.1 as the experimental class (30 students) and VIII.2 as the control class (30 students). The instrument used was a motivation questionnaire with a 16-item Likert scale. The data were analyzed using SPSS, applying paired sample t-test and independent sample t-test to determine the effect of ice breaking on students’ motivation. The results showed a significant effect of using ice breaking on students’ motivation in English learning. The paired sample t-test for the experimental group showed Sig. (2-tailed) = 0.000 < 0.05, indicating that Ha was accepted. The independent sample t-test also revealed Sig. (2-tailed) = 0.000 < 0.05, confirming a significant difference between the experimental and control classes. These findings indicate that using ice breaking is more effective in improving students’ motivation compared to conventional teaching methods.